Global scale transcriptome analysis reveals differentially expressed genes involve in early somatic embryogenesis in Dimocarpus longan Lour - Chen, Yukun (BMC Genomics, 2020)
BACKGROUND: Somatic embryogenesis (SE) is a process of somatic cells that dedifferentiate to totipotent embryonic stem cells and generate embryos in vitro. Longan SE has been established and wildly used as model system for studying embryogenesis in woody plants, SE-related genes had been characterized. In spite of that, a comprehensive overview of SE at a molecular level is still absent. To understand the molecular mechanisms during longan SE, we examined the transcriptome changes by using Illumina HiSeq from the four distinct developmental stages, including non-embryogenic callus (NEC), embryogenic callus (EC), incomplete compact pro-embryogenic cultures (ICpEC), globular embryos (GE). RESULTS: RNA-seq of the four samples generated a total of 243.78 million high quality reads, approximately 81.5% of the data were mapped to longan genome. The cDNA libraries of NEC, EC, ICpEC and GE, generated 22,743, 19,745, 21,144, 21,102 expressed transcripts, 1935, 1710, 1816, 1732 novel transcripts, 2645, 366, 505, 588 unique genes, respectively. Comparative transcriptome analysis showed that a total of 10,642, 4180, 5846 and 1785 genes were differentially expressed in the pairwise comparisons of NEC_vs_EC, EC_vs_ICpEC, EC_vs_GE, ICpEC_vs_GE, respectively. Among them, plant hormones signalling related genes were significantly enriched, especially the auxin and cytokinin signalling components. The transcripts of flavonoid biosynthesis related genes were mainly expressed in NEC, while fatty acid biosynthesis related genes mainly accumulated in early SE. In addition, the extracelluar protein encoding genes LTP, CHI, GLP, AGP, EP1 were related to longan SE. Combined with the FPKM value of longan nine tissues transcription, 27 SE specific or preferential genes (LEC1, LEC1-like, PDF1.3, GH3.6, AGL80, PIN1, BBM, WOX9, WOX2, ABI3, et al.) and 28 NEC preferential genes (LEA5, CNOT3, DC2.15, PR1–1, NsLTP2, DIR1, PIP1, PIP2.1, TIP2–1, POD-P7 and POD5 et al.) were characterized as molecular markers for longan early SE. qRT-PCR validation of SE-related genes showed a high correlation between RNA-seq and qRT-PCR data. CONCLUSION: This study provides new insights into the role of the transcriptome during early SE in longan. Differentially expressed genes reveal that plant hormones signalling, flavonoid and fatty acid biosynthesis, and extracelluar protein related genes were involved in longan early SE. It could serve as a valuable platform resource for further functional studies addressing embryogenesis in woody plants.